Le contexte alchimique des Noces Chymiques - Didier Kahn (Recherches Germaniques, 2018)
The myth of Christian Rosencreutz developed at a time when the number of fictitious authors of alchemical treatises, self-styled disciples or precursors of Paracelsus, increased considerably. A comparison with Basilius Valentinus’ and Salomon Trismosin’s myths enables us to understand the alchemical context in which Andreae’s text was created. Furthermore, three years after Ratich Brotoffer’s Elucidarius, the anonymous author of the Practica leonis viridis (1619) attempted to interpret part of the Chymical Wedding from an alchemical point of view. While it is not our intention to promote such a perspective as the only valid interpretation key, we nevertheless intend to illustrate the influence of alchemy on the genesis as well as on the reception of the Chymical Wedding.